2020
DOI: 10.1155/2020/1835352
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Oxidative Stress in Patients with Difficult-to-Heal Skin Wounds Treated with Hyperbaric Oxygen

Abstract: Objective. To determine the concentration of thiobarbituric acid reactive substances (TBARS) in erythrocytes and blood plasma, and the activities of selected antioxidant enzymes: catalase (CAT), superoxide dismutase (SOD), and glutathione peroxidase (GPx) in erythrocytes in patients receiving hyperbaric oxygen (HBO) treatment due to difficult-to-heal “skin wounds”. Material and Methods. Indices of oxidative stress were assessed in venous blood taken from 23 patients three times: immediately before HBO procedur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…The outcome showed a decrease which was significant in MDA between the last session of day 20 and day one. (27) Although using a lower HBO pressure and shorter time per session, as well as a longer duration of therapy, the results are the same as this study which showed that HBO therapy could reduce MDA levels.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The outcome showed a decrease which was significant in MDA between the last session of day 20 and day one. (27) Although using a lower HBO pressure and shorter time per session, as well as a longer duration of therapy, the results are the same as this study which showed that HBO therapy could reduce MDA levels.…”
Section: Discussionsupporting
confidence: 75%
“…(26) This treatment increments the expression of diverse growth factors. (27) The use of HBO therapy shows a hormetic effect by inducing reactive oxygen species (ROS) at moderate levels. (28) Moderate concentrations of ROS are useful for cell signaling and the immune system.…”
Section: Introductionmentioning
confidence: 99%
“…Diabetic ulceration is a common diabetic complication, and it causes chronic wound infection that is a serious medical problem that threatens the health and quality of life of diabetic patients [ 3 5 ]. ROS are generated during incomplete oxygen metabolism, and under diabetic conditions, immune cells increase ROS levels in the wound microenvironment, leading to stubborn scars and prolonged wounds [ 6 8 ]. The superfluous ROS within the impaired wound can promote intense inflammatory reactions to make the wounds fragile, but also restricts skin regeneration by stem cells and macrophages [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these challenges, it is crucial to develop effective treatments that can simultaneously target bacterial infections and scavenge excessive ROS, promoting the recovery of diabetic wounds.In cellular enzyme-involved metabolism, oxygen undergoes a series of one-electron reactions, which alternately leads to the formation of several kinds of ROS, including superoxide anion (O 2 •− ), hydroxyl radical (OH·), and hydrogen peroxide (H 2 O 2 ). To defend against excessive ROS, the body has endogenous antioxidases, such as catalase (CAT), SOD, and GPx, are capable of catalyzing the disproportionation reactions of O 2 •− and H 2 O 2 into H 2 O [ 6 , 13 , 14 ]. However, these natural enzymes are usually unstable, with a short half-life in circulation, and are hard to be adequately produced in wound [ 15 ].…”
Section: Introductionmentioning
confidence: 99%